2014
DOI: 10.14814/phy2.12001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of obesity and hypoxia on left ventricular function and glycolytic metabolism

Abstract: We have previously reported that 4 weeks of intermittent hypoxia (IH) exposure, mimicking the hypoxic stress of obstructive sleep apnea, produces compensatory increases in left ventricular (LV) contractility in lean C57BL/6J mice. In this study we compared the effects of 4 weeks IH to 4 weeks of sustained hypoxia (SH) on LV function and cardiac glycolysis in lean C57BL/6J mice and obese ob/ob mice at 10–12 weeks of age. The four exposure conditions were IH (nadir O2 [5–6%] at 60 cycles/h during the 12 h light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
3
8
0
Order By: Relevance
“…This was associated with increased cardiac interstitial fibrosis, but no cardiac hypertrophy. These results are in accordance with previous studies demonstrating that 4 weeks IH increased cardiac contractility, independently of cardiac hypertrophy (Naghshin et al, 2009(Naghshin et al, , 2012Rodriguez et al, 2014), whereas other studies demonstrated cardiac remodeling (i.e. apoptosis, interstitial fibrosis, hypertrophy) and contractile dysfunction (i.e., reduction in ejection fraction) (Chen et al, 2008(Chen et al, , 2010 upon IH exposure.…”
Section: Ih In Lean Micesupporting
confidence: 93%
See 1 more Smart Citation
“…This was associated with increased cardiac interstitial fibrosis, but no cardiac hypertrophy. These results are in accordance with previous studies demonstrating that 4 weeks IH increased cardiac contractility, independently of cardiac hypertrophy (Naghshin et al, 2009(Naghshin et al, , 2012Rodriguez et al, 2014), whereas other studies demonstrated cardiac remodeling (i.e. apoptosis, interstitial fibrosis, hypertrophy) and contractile dysfunction (i.e., reduction in ejection fraction) (Chen et al, 2008(Chen et al, , 2010 upon IH exposure.…”
Section: Ih In Lean Micesupporting
confidence: 93%
“…In addition, contrary to lean mice, IH did not increase cardiac contractility in obese mice, which could traduce that obese mice cannot develop an adaptive cardiac response to IH. Same results were reported by Rodriguez et al who demonstrated that ob/ob mice failed to develop a compensatory contractile response to IH (Rodriguez et al, 2014). Besides, in this study, the authors demonstrated that obese mice were unable to increase glycolytic rate, which was proposed as an adaptive mechanism in lean mice (Rodriguez et al, 2014).…”
Section: Ih In Diet-induced Obese Micesupporting
confidence: 83%
“…In contrast, indices of cardiac function (stroke volume, cardiac output, ejection fraction) were relatively maintained throughout ischemia/reperfusion in obese swine and thus, were significantly higher in obese vs. lean swine (Table 3). Again, this preservation of ventricular stroke volume and pressure generation was observed despite the nonsignificantly greater infarct size as measured by troponin I (Table 2) as well as the presumed presence of an obesity cardiomyopathy phenotype which one might predict to observe in these animals a priori [3, 54]. Overall these data suggest that the relative preservation of ventricular function under ischemia/reperfusion in our model of early obesity was achieved via a Frank-Starling mechanism (increase end-diastolic filling volume) to maintain cardiac output in response to an ischemia/reperfusion insult (Figures 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a complex disease state that is accompanied by a number of cardiac disease risk factors including hypertension and metabolic dysregulation (glucose intolerance, insulin resistance, dyslipidemia)[54] that are associated with pathologic changes in the heart (ventricular hypertrophy, heart failure)[6, 16, 34, 65] and in the vasculature (atherosclerosis, microvascular dysfunction)[8, 31, 60]. In prospective clinical studies, overweight or obese individuals have increased rates of cardiovascular diseases [1, 3, 41], contributing to a 2–3 fold increase in overall mortality relative to normal weight individuals[1, 7, 15, 32, 49, 51].…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the role of gender in modifying the observed relationship between pulmonary function and cardiovascular outcomes might operate via the proposed mechanisms that link the pathogenesis of pulmonary disease and cardiovascular disease [11]. Oxidative stress induced by both chronic intermittent hypoxia and sustained hypoxia has been found to cause left ventricular dysfunction in murine models of obstructive sleep apnea and pulmonary disease [26,27]. Inflammationsensitive plasma proteins in addition to arterial inflammation have been explored as a partial mediator of the relationship between pulmonary function and cardiovascular risk, but serum biomarkers do not completely account for the magnitude of the increase in cardiovascular risk observed in individuals with reduced FVC [28e30].…”
Section: Tablementioning
confidence: 99%